2013
DOI: 10.1128/aac.00372-13
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Method To Rapidly Assay Bacterial Persister Metabolism

Abstract: Bacterial persisters exhibit an extraordinary tolerance to antibiotics that is dependent on their metabolic state. Although persister metabolism promises to be a rich source of antipersister strategies, there is relatively little known about the metabolism of these rare and transient phenotypic variants. To address this knowledge gap, we explored the use of several techniques, and we found that only one measured persister metabolism. This assay was based on the phenomenon of metabolite-enabled aminoglycoside k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
182
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 119 publications
(202 citation statements)
references
References 30 publications
16
182
3
1
Order By: Relevance
“…The vast majority of persisters are dormant (7), and within such a state AGs are ineffective (9). In previous work, we discovered that specific metabolites produce AG killing of persisters and that such potentiation is dependent on catabolism of the substrate to generate proton motive force through respiration (9,10). This study demonstrated that persisters are metabolically active, and we have since shown that the assay can be used to measure the metabolism of persisters from antibiotic-treated cultures.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…The vast majority of persisters are dormant (7), and within such a state AGs are ineffective (9). In previous work, we discovered that specific metabolites produce AG killing of persisters and that such potentiation is dependent on catabolism of the substrate to generate proton motive force through respiration (9,10). This study demonstrated that persisters are metabolically active, and we have since shown that the assay can be used to measure the metabolism of persisters from antibiotic-treated cultures.…”
Section: Resultsmentioning
confidence: 95%
“…Notably, the approach circumvents the need to segregate persisters from other cell types, because within antibiotic-treated populations that have reached the second regime of biphasic killing, the only cells that remain culturable are persisters. Therefore, survival data from samples treated with an AG with or without a metabolite can be used to infer persister catabolism (10). Using this assay, we analyzed the impacts of ⌬arcA, ⌬cra, ⌬crp, ⌬dksA, ⌬fnr, ⌬lrp, and ⌬rpoS on the ability of persisters to consume carbon sources and generate proton motive force aerobically.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations